The Influence Of Incentives, Work Motivation And Turnover Intention On Employee Performance At PT Startmara Pratama Batam - Fernando Fernando; M Khoiri (Economics and Digital Business Review, 2024)
This research was conducted to find out the effect of incentives, work motivation and turnover intention on employee performance at PT Startmara Pratama Batam where each variable has problems such as a lack of motivation in the workplace, so that the incentives given do not match the agreement from the start. This type of research is quantitative research to test the relationship between variables. This research has a population with the number of customers of PT Startmara Pratama Batam in 2023, namely 127 employees at PT Startmara Pratama Batam. This research uses a purposive sampling method. The results of this research show that the variables Incentive, Work Motivation and Turnover Intention are significantly positive on employee performance.